A study of in-process waiting time on a linear walking worker assembly line - Lassalle, S; Wang, Q; Owen, G W; Mileham, A R (Proceedings of the Institution of Mechanical Engineers. Part B, Journal of engineering manufacture, 2007)
Abstract This paper presents a study of in-process waiting times on a linear walking worker assembly line in a real buffer-constrained flowshop environment using the simulation method. The in-process waiting time can lead to production loss and in-process inventory; it can also affect the throughput time for completion of a product assembled in a sequential flowline-based manufacturing system. The aim of this research is to investigate the varying magnitude of the total in-process waiting time for individual walking workers who may have to wait to carry out operations at a station due to blocking on the line ahead. The results were obtained by varying a number of system parameters embedded in a simulation model created using Witness® with the key input/output data being manipulated by a series of MS Excel-spreadsheets. The main finding of this work is that the in-process waiting time (which affects the expected throughput time) can be determined and it is adjustable by the strategic application of walking workers on a linear assembly line, even if the system behaviour is random.